OP0086 The fully human anti-tnf monoclonal antibody, adalimumab (d2e7), dose ranging study: the 24-week clinical results in patients with active ra on methotrexate therapy (the armada trial). (1st June 2001) - Keystone, E; Weinblatt, ME; Weisman, M; Furst, D; Paulus, H; Birbara, C; Fischkoff, S; Chartash, EK
Abstract : Background: Objectives: To investigate the clinical efficacy and safety of adalimumab (D2E7), given subcutaneously in combination with methotrexate (MTX) to rheumatoid arthritis (RA) patients who are partial responders to MTX treatment. Methods: The ARMADA Trial was a double-blind placebo controlled study of 271 patients who had active RA despite concurrent stable doses of MTX. The patients were randomised to receive placebo or the fully human anti TNF monoclonal antibody, adalimumab (D2E7), at one of 3 doses (20, 40 and 80 mg every other week). Baseline demographic characteristics included: 76.8% females, 81% rheumatoid factor positivity, mean age 55.5 years, mean duration of RA 12.3 years, mean dose of MTX 16.8 mg/week, mean number of previous DMARDs 3.0. These characteristics were well matched between treatment groups. Results: Clinical efficacy results for the placebo controlled 24-week period are displayed in the Table 1 below. Adverse events in the adalimumab (D2E7) groups are similar to placebo. Only injection site reactions occurred more frequently with adalimumab (D2E7) in 14.8% of the patients versus 3.2% in the placebo group. Conclusion: The efficacy of the fully human anti-TNFα monoclonal antibody, adalimumab (D2E7), in addition to MTX in patients with longstanding RA is significantly better than placebo when given every other week subcutaneously. The ACR50 and ACR70 responses were impressive in this group of patients with refractory RA.